Studying the Characteristics of Curcumin-Loaded Liposomal Nanoparticles - Afyouni, Iman; Ghanbarikondori, Parizad; Sadeghi Pour, Niki; Mir Hashemian, Paria; Jalali, Fereshtehsadat; Sedighi, Armin; Allahyartorkaman, Mohammadreza (Asian Pacific Journal of Cancer Biology, 2024)
Background: In this study, the physical and chemical properties of curcumin are extensively examined when it is incorporated into liposome nanoparticles, to enhance its therapeutic potency and bioavailability. Curcumin, a plant-derived polyphenol, has garnered attention for its anti-inflammatory, antioxidant, and anti-cancer activities. However, its clinical utility is hindered by several limitations, including poor water solubility, inadequate absorption, and rapid metabolism. By leveraging the potential of liposome nanoparticles to improve drug delivery and efficacy, this research aims to overcome these obstacles and unlock the full therapeutic potential of curcumin. Methods: Curcumin-loaded liposome nanoparticles (CLLNs) were fabricated employing a thin-film hydration method, after sonication. The physicochemical attributes of CLLNs were subsequently characterized, encompassing particle size and zeta potential assessment utilizing dynamic light scattering (DLS), encapsulation efficiency (EE%) and drug loading efficiency (DLE%) determination through high-performance liquid chromatography (HPLC), investigation of in vitro drug release patterns in simulated biological fluids. Results: The CLLNs optimized in this study had a mean particle diameter of less than 250 nm and a negative surface charge, implying good stability and potential for cellular uptake. The encapsulation efficiency and drug loading efficiency were both found to be high, indicating that curcumin was effectively loaded into the liposomes. In vitro release testing showed a sustained release pattern of curcumin from the CLLNs. Conclusion: The research offered important observations about the advantageous physicochemical features of curcumin-loaded liposome nanoparticles, highlighting their potential as a cutting-edge delivery system for curcumin. The study demonstrated that CLLNs have high encapsulation and drug loading efficiencies, as well as controlled release and improved stability, which suggests their ability to enhance the therapeutic benefits of curcumin. These findings set the stage for future in vivo and clinical trials to fully investigate the potential of CLLNs in medical applications.